2017
DOI: 10.1200/po.17.00010
|View full text |Cite
|
Sign up to set email alerts
|

Parental Perspectives on Whole-Exome Sequencing in Pediatric Cancer: A Typology of Perceived Utility

Abstract: Purpose To explore how parents of pediatric patients with cancer perceived the utility of clinical tumor and germline whole-exome sequencing (WES) results. Patients and Methods We conducted longitudinal interviews with parents of a diverse pediatric cancer population before disclosure of WES results (n = 64), then 1 to 8 months (n = 33) after disclosure. Interview transcripts were analyzed using a thematic qualitative approach. Results Parents identified a broad range of types of utility for their child’s WES … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(65 citation statements)
references
References 25 publications
4
61
0
Order By: Relevance
“…37 There have been several attempts to understand barriers to productive physician-patient interactions about genomic information. Whether in commentaries, 4,8,11,12,24,26,40,42 systematic reviews, 10, 17 surveys, 7,9,43 qualitative work, 18, 25, 44 -49 or essays, 23,50 previous work has largely been focused on the perspectives of physicians, 4, 7 -10, 12, 17, 18, 23 -25 patients, 43,44 or parents 45,46,48,49 but rarely on the perspectives of 2 or more of these groups simultaneously. 47, 50 -52 In practice, however, the sharing of genetic test results occurs within the context of a clinical interaction between physicians and patients or between physicians, patients, and parents.…”
mentioning
confidence: 99%
“…37 There have been several attempts to understand barriers to productive physician-patient interactions about genomic information. Whether in commentaries, 4,8,11,12,24,26,40,42 systematic reviews, 10, 17 surveys, 7,9,43 qualitative work, 18, 25, 44 -49 or essays, 23,50 previous work has largely been focused on the perspectives of physicians, 4, 7 -10, 12, 17, 18, 23 -25 patients, 43,44 or parents 45,46,48,49 but rarely on the perspectives of 2 or more of these groups simultaneously. 47, 50 -52 In practice, however, the sharing of genetic test results occurs within the context of a clinical interaction between physicians and patients or between physicians, patients, and parents.…”
mentioning
confidence: 99%
“…The introduction of massively parallel NGS has enabled the simultaneous examination of more than 100 genes, in which actionable mutations have been detected. Clinical laboratories in the USA have developed and implemented a variety of NGS‐based tests (tumor‐profiling multiplex gene panels), ranging from targeted “hotspot” panels (Table ) to comprehensive genome‐scale platforms …”
Section: Clinical Sequencing Using Next‐generation Sequencing (Ngs) Pmentioning
confidence: 99%
“…Clinical laboratories in the USA have developed and implemented a variety of NGS-based tests (tumor-profiling multiplex gene panels), ranging from targeted "hotspot" panels ( Table 1) to comprehensive genome-scale platforms. [13][14][15][16] To ensure that the results can be applied in clinical practice, these NGS-based tests are carried out in Clinical Laboratory F I G U R E 1 Discovery of RET fusion and its translation to clinical oncology. RET fusion was discovered in 2012.…”
Section: Clinical Sequencing Using Next-gen Eration Sequencin G (Ngmentioning
confidence: 99%
“…Just a few years ago, it seemed that North American parents were very interested in sequencing their children's genomes. Parents of children who were sick and had various underlying health conditions reported high interest in learning as much as possible about their children's genomes, as did pregnant women and their partners . Survey research in the United States published in 2013 and 2014 reported that most parents would welcome expanded screening or sequencing of their newborn babies .…”
Section: Essaymentioning
confidence: 99%